PERANCANGAN SISTEM E-BUSINESS BERBASIS GAMIFIKASI UNTUK MENINGKATKAN ENGAGEMENT PELANGGAN PADA UMKM TROPICAL CHIPS - Putri Prasetyningrum; Ozzi Suria (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Digital transformation encourages MSMEs to develop e-business strategies that focus not only on online sales but also on enhancing customer engagement and loyalty. This study aims to design and evaluate a gamification-based e-business system for the Tropical Chips MSME to increase user interaction and encourage repeat purchases. The research method used is Research and Development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The developed system integrates gamification features, including points, badges, challenges, a progress bar, and rewards into the e-business website. The system was tested on 30 respondents, consisting of prospective users or potential customers of Tropical Chips, using black-box testing, usability testing, and user engagement measurement. The testing results showed that all main system features met the functional requirements, with a 100% success rate in black-box testing. The usability testing results achieved a feasibility percentage of 86.5%, indicating that the system falls into the highly feasible category. The user engagement measurement showed that 83.3%of users actively used the gamification features, while 80.0% of respondents stated that these features increased their interest in making repeat purchases. This study develops an integrated e-business model that combines SWOT, PIECES, and PESTEL analyses with gamification features to improve customer engagement in food-sector MSMEs. Based on these results, it can be concluded that implementing gamification in the Tropical Chips e-business system can increase user engagement, enhance the customer experience, and support MSME competitiveness in the digital business era.